Configuration school in strategy management: a bibliometric literature review (Research, Society and Development, 2022)
Strategic management does not have a consolidated concept, but some relevant definitions from different authors. This research aims to conduct a quantitative and qualitative study, through a literature review of the relationship between the configuration school in the business strategy. Based on the book "Strategy Safari" by the authors Mintzberg, H; Ahlstrand, B.W.; & Lampel J. (1998), a review of the existing literature on strategic management and configuration school was carried out. The tenth school, the configuration school, is recognized with the combination of the other nine. Using the words “Strategy” and “Configuration School” in the search on Scopus bibliographic database, was made the selection of articles for bibliometric analysis, excluding those that were not related to strategic management theme. The analysis was carried out with VOSviewer program and with interpretation of the data in the cluster concept. As descriptive results are 194 articles published from 1978 to 2021, most of them published in the United States, followed by the United Kingdom and Australia. Regarding the evaluative results, a cluster with six groups of keywords and terms in co-occurrence and another cluster of co-citations that presents the most relevant authors, with Brazilian or Portuguese-speaking authors not being among the main ones in this line of research.